Pembuatan Soal AKM Berstandar PISA MGMP Matematika SMP Kabupaten Kudus - widya kusumaningsih; Supandi; lilik ariyanto (Khaira Ummah, 2022)
The aims of this community service are to be able to improve the ability of the teachers in the Mathematics MGMP of the Kudus Regency Junior High School in making AKM with PISA standards. This is necessary because one of the indicators used as a reference in the Ministry of Education and Culture (Kemendikbud) in assessing student learning is the PISA. PISA as an international assessment method is an indicator to measure the competence of Indonesian students at the global level. This is a challenge for education in Indonesia. So, it is necessary to have a way to test or assess the quality of learning outcomes that are appropriate and can be seen from various aspects of the lesson. This assessment is called the Minimum Competency Assessment, which will focus on information text literacy, data literacy and numeracy literacy, and character education. The results obtained from this service are the improvement of the skills of the Mathematics MGMP teachers at the Kudus Regency Junior High School in making the PISA standard